Light and photosynthesis in aquatic ecosystems - Kirk, John T. (Cambridge University Press / New York, 1983)
Contents: Concepts of hydrological optics; Incident solar radiation; Absorption of light within the aquatic medium; Scattering of light within the aquatic medium characterizing the underwater light field; The nature of the undewater light field; remote sensing of the aquatic environment; Photosynthesis in the aquatic environment; light capture by aquatic plants